The effect of cryotherapy on nerve conduction velocity, pain threshold and pain tolerance - Algafly, Amin A; George, Keith P (British journal of sports medicine, 2007)
Objectives: To determine the impact of the application of cryotherapy on nerve conduction velocity (NCV), pain threshold (PTH) and pain tolerance (PTO). Design: A within-subject experimental design; treatment ankle (cryotherapy) and control ankle (no cryotherapy). Setting: Hospital-based physiotherapy laboratory. Participants: A convenience sample of adult male sports players (n = 23). Main outcome measures: NCV of the tibial nerve via electromyogram as well as PTH and PTO via pressure algometer. All outcome measures were assessed at two sites served by the tibial nerve: one receiving cryotherapy and one not receiving cryotherapy. Results: In the control ankle, NCV, PTH and PTO did not alter when reassessed. In the ankle receiving cryotherapy, NCV was significantly and progressively reduced as ankle skin temperature was reduced to 10°C by a cumulative total of 32.8% (p<0.05). Cryotherapy led to an increased PTH and PTO at both assessment sites (p<0.05). The changes in PTH (89% and 71%) and PTO (76% and 56%) were not different between the iced and non-iced sites. Conclusions: The data suggest that cryotherapy can increase PTH and PTO at the ankle and this was associated with a significant decrease in NCV. Reduced NCV at the ankle may be a mechanism by which cryotherapy achieves its clinical goals.